Mycobacterium lepromatosis Lepromatous Leprosy in US Citizen Who Traveled to Disease-Endemic Areas - Virk, Abinash (Emerg Infect Dis, 2017)
We report Mycobacterium lepromatosis infection in a US-born person with an extensive international travel history. Clinical symptoms, histopathology, and management are similar to those of infections caused by M. leprae. Clinicians should consider this pathogen in the diagnosis of patients with symptoms of leprosy who have traveled to endemic areas.